Translational control of phloem development by RNA G-quadruplex-JULGI determines plant sink strength - Cho, Hyunwoo; Wallner, Eva-Sophie; Greb, Thomas (Nature plants, 2018)
RNA G-quadruplex is a secondary RNA structure formed by G-rich sequences. Now a zinc-finger protein has been identified to target the G-quadruplex motifs of two key factors in phloem differentiation, leading to a new translational regulatory pathway.
Published: 28 May 2018
Gesehen am 02.05.2019